RITUAL PETIK LAUT DAN KERAGAMAN (KERAGAMAN DAN KOMUNIKASI RITUAL DI KALANGAN NELAYAN MULTIETNIS DI KEDUNGREJO MUNCAR BANYUWANGI) - Nur Ainiyah (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2017)
This research purpose to show how ritual communication in cultural social diversity of fi sherman community of Kedungrejo Muncar Banyuwangi going in harmony. As a result, collective ritual of Petik Laut become a media of communication and integration within variety of fi sherman community. The focuses of research are: 1. How reality of ritual of Kedungrejo fi sherman community?, 2. How cultural social diversity in the community be build?, 3. How ritual communication become a media of integration within this multi ethnic cultural community?. This research describes that the ideology is a signifi cant problem for coastal society caused of their character. Coastal communitues, generally known for being violent and open to religious and ideological diversity. Ritual communication as an integration media for cultural social community can be seen in implementation of Petik Laut collective ritual. It shows the coastal Islamic cosmology that communication on ritual erase social cultural border in their community. Keywords: Ritual, Plurality, Communication and Cosmology